Aerobic culture results of samples taken during lumbar disc herniation operations (Annals of Medical Research, 2021)
Aim: This study aimed to determine the rate of aerobic bacterial infection in disc samples taken from the surgical field in patients with lumbar disc herniation (LDH) undergoing single-level lumbar microdiscectomy (LMD).Material and Methods: Disc tissue samples were collected from the surgical fields in patients with single-level LDH undergoing elective LMD between September 2019 and May 2020. Tissues were then cultivated in cultures to determine the rate of aerobic bacteria and the results obtained were noted. The effects of parameters such as age, gender, affected side, Modic changes (MCs), and accompanying systemic diseases on culture results were statistically investigated. The patients were examined retrospectively with their demographic values. Results: This study included 33 patients with single-level LDH and all of these patients underwent LMD. Two patients additionally underwent posterior lumbar instrumentation. The mean age was 50.87±12.20 years (25-71 years) and 17 (51.51%) of the patients were men and 16 (48.49%) were women. The mean follow-up duration was 3.03±1.64 months (1–8 months). Aerobic infection was observed in four patients (12.12%). Two of them (6.06%) were Enterobacteriaceae and the other two (6.06%) were coagulase-negative staphylococci (CNS). The antibiotic that patients were sensitive to was added to the postoperative medical treatment for two weeks according to the culture and antibiogram results. Age, gender, affected side, MC, and accompanying systemic diseases were found to have no statistically significant effect on culture results.Conclusion: The prevalence of subclinical aerobic bacterial infection has been found to be 12.12% in patients undergoing LMD. Although sterilization rules have been strictly followed, the possibility of contamination of disc cultures could have not been completely rejected. In conclusion, the present study has shown that culture results have no effect on postoperative outcomes.